Aluminium parts from scrap using new technique - Mohammed Misbahul, Amin; Ku Halim, Ku Bulat; Hamdan, Suhaimi (Journal of Ultra Scientist of Physical, 2009)
Link to publisher's homepage at http://www.ultrascientist.org/